The Promise and Pitfalls of Conflict Prediction: Evidence from Colombia and Indonesia - Bazzi, Samuel; Blair, Robert A.; Blattman, Christopher; Dube, Oeindrila; Gudgeon, Matthew; Peck, Richard (The Review of Economics and Statistics, 2022)
How feasible is violence early-warning prediction? Colombia and Indonesia have unusually fine-grained data. We assemble two decades of local violent events alongside hundreds of annual risk factors. We attempt to predict violence one year ahead with a range of machine learning techniques. Our models reliably identify persistent, high-violence hot spots. Violence is not simply autoregressive, as detailed histories of disaggregated violence perform best, but socioeconomic data substitute well for these histories. Even with unusually rich data, however, our models poorly predict new outbreaks or escalations of violence. These “best-case” scenarios with annual data fall short of workable early-warning systems.